Effect of annealing and heat-moisture pretreatment on the quality of 3D-printed wheat starch gels. (March 2023) - Zheng, Luyao; Zhang, Qianru; Yu, Xiuzhu; Luo, Xiaohu; Jiang, Hao
Abstract: This paper examines the effects of annealing treatment (ANN) and heat-moisture treatment (HMT) on the physicochemical and structural properties of wheat starch used for 3D food printing. Printing performance, molecular weight (Mw), amylopectin branch chain length distribution, pasting properties, rheology, fourier transform infrared (FT-IR) spectroscopy, texture and scanning electron microscopy (SEM) were used to evaluate the quality of printed products. Compared to untreated wheat starch, HMT improved the accuracy of 3D printing, stacking height of printed samples, and prolonged storage time of printed sample with softer texture. Conversely, ANN decreased printing performance, made sample edges rougher, reduced the stacking height of printed samples, and significantly increased sample hardness in storage. These effects are consistent with changes that these treatments made to the Mw of starch: compared to native starch and ANN, HMT increased the Mw of amylose and significantly decreased average Mw. In turn, this change decreased viscosity and G' of the starch gel, enabling smoother extrusion and better printing lines. In conclusion, HMT can improve 3D printing performance of wheat starch, increasing printing height and accuracy, which provides a simple and effective method to improve 3D printing effect using starch. Highlights: HMT wheat starch gel had the maximum deposition height and printing accuracy. ANN significantly hindered wheat starch gel to achieve 3D printing of higher model. The increase of amylose molecular weight benefited to 3D-printed effect of gels. Low viscosity with small extruded line width, related to better printing accuracy. HMT gel had a denser network structure to keep the shape of a printed sample.